Allosteric effects on oxidative and nitrosative reactions of cell-free hemoglobins - Bonaventura, Celia; Henkens, Robert; Alayash, Abdu I; Crumbliss, Alvin L (IUBMB life, 2007)
A review of the oxidative and nitrosative reactions of cell-free hemoglobin-based oxygen carriers (HBOCs) shows that these reactions are intimately linked and are subject to allosteric control. Cross-linking reactions used to produce HBOCs introduce conformational constraints and result in Hbs with reduced responses to heterotropic and homotropic allosteric effectors. The Nernst plots of heme oxidation of cross-linked HBOCs are shifted to higher potentials relative to unmodified Hb in the absence of allosteric effectors, in accord with their T-state stabilization and right-shifted Hill plots of O(2) binding. They exhibit enhanced rates of autoxidation and nitrite-induced oxidation, features that appear due to their having more solvent-accessible heme pockets. The stability of their NO-Hb derivatives varies as a result of allosteric effects on the extent of formation of pentacoordinate NO-heme geometry by alpha chains and subsequent oxidation of partner beta chains. The physiological implications of these findings on the safety, efficacy and design of second generation HBOCs are discussed in the framework of a reaction scheme showing linkages between Hb-mediated redox reactions. These redox reactions can drive formation of SNO-Hb and other reactive species and are of significance for the use of cell-free Hbs in vivo.